Determinants of participation in voluntary work: a systematic review and meta-analysis of longitudinal cohort studies - Jacobien Niebuur; Lidy van Lente; Aart C. Liefbroer; Nardi Steverink; Nynke Smidt (BMC Public Health, 2018)
Abstract Background Participation in voluntary work may be associated with individual and societal benefits. Because of these benefits and as a result of challenges faced by governments related to population ageing, voluntary work becomes more important for society, and policy measures are aimed at increasing participation rates. In order to effectively identify potential volunteers, insight in the determinants of volunteering is needed. Therefore, we conducted a systematic review including meta-analyses. Methods A systematic search in MEDLINE, PsycINFO, SocINDEX, Business Source Premier, and EconLit was performed on August 12th 2015. We included longitudinal cohort studies conducted in developed countries that quantified factors associated with volunteering among samples from the general adult population. Two reviewers independently selected eligible studies, extracted the data and assessed the risk of bias of the included studies using the QUIPS tool. Estimates reported in the papers were transformed into Odds Ratios and 95% Confidence Intervals. For each determinant, random-effects meta-analyses were used to generate summary estimates. Results We found that socioeconomic status, being married, social network size, church attendance and previous volunteer experiences are positively associated with volunteering. Age, functional limitations and transitions into parenthood were found to be inversely related to volunteering. Conclusions Important key factors have been identified as well as gaps in the current literature. Future research should be directed towards deepening the knowledge on the associations between the factors age, education, income, employment and participation in voluntary work. Moreover, major life course transitions should be studied in relation to volunteering.